HUKUM ISLAM DAN DINAMIKA SOSIAL ‎ : ‎(Studi Analisis Metode Penemuan Hukum Islam Kontekstual)‎ - Nairi Saadah; M. Hasbi Umar; Ramlah (Jurnal Indragiri Penelitian Multidisiplin, 2023)
This research examines the renewal of contextual Islamic law discovery methods that function to answer the challenges of the times and social dynamics. As an initial step in the reconstruction of fiqh, this research seeks to explain a solution offered by fiqh methods, namely a unified approach to shari'ah and social inference. In simple terms, this method seeks to bridge and integrate textual (normative) and contextual (historical-empirical) approaches. The basic assumption is that this effort will be beneficial for alternative methods of discovering Islamic law in this multi-cultural and religious era. This research is a literature study (library research) using a juridical, historical, and philosophical approach to answer the problems above. This study concludes that there are three methods of ijtihad, namely bayani (linguistics), ta'lili (qiyasi: causation), and istislahi (teleological). These three are common methods used in discovering and forming fiqh civilizations from time to time. By bringing empirical reality into the analysis of legal findings, there will be little guarantee that Islamic law in Indonesia can appear more creative and alive in the midst of modern social regulatory processes. As for the effort to renew the method of discovering Islamic law with a contextual approach in the form of historical and textual inference analysis, this is an ideal intellectual achievement. there will be little guarantee that Islamic law in Indonesia can appear more creative and live in the midst of modern social regulatory processes. As for the effort to renew the method of discovering Islamic law with a contextual approach in the form of historical and textual inference analysis, this is an ideal intellectual achievement. there will be little guarantee that Islamic law in Indonesia can appear more creative and live in the midst of modern social regulatory processes. As for the effort to renew the method of discovering Islamic law with a contextual approach in the form of historical and textual inference analysis, this is an ideal intellectual achievement